Dispersing carbomers, mixing technology matters!. Issue 13 (10th March 2022) - Houlleberghs, Maarten; Verheyden, Loes; Voorspoels, Filip; Chandran, C. Vinod; Duerinckx, Karel; Radhakrishnan, Sambhu; Martens, Johan A.; Breynaert, Eric
Abstract : Magnetohydrodynamic mixing yields carbomer dispersions with higher viscosity and higher storage modulus as compared to high shear mixing. 1 H NMR reveals molecular level differences in water distribution, polymer degradation and charge stabilization. Abstract : Mixing dry carbomer powder with water using magneto-hydrodynamic mixing yielded carbomer dispersions with higher viscosity and increased storage modulus as compared to conventional high shear mixing. 1 H NMR spectroscopy demonstrated this to be induced by a different water distribution, accompanied by lower ionization and higher degradation of the polymer in case of high shear mixing. This investigation reveals 1 H MAS NMR to provide suitable sensitivity and resolution to detect structural changes induced in organic polymers during their hydration.